Tuberculous meningitis in childhood: clinical and computerized tomography scan manifestations - Gürses, Nuran; Özkan, Ayşen; Diren, Barıs (The Turkish Journal of Pediatrics, 1987)
Twelve cases with tuberculous meningitis were studied by the use of computerized tomography. The clinical and CT findings are presented and discussed. The conclusion was reached that CT should be included in diagnostic and follow-up studies of tuberculous meningitis.